Applicability of Lean Healthcare in Sri Lankan Healthcare Supply Chains - Rangi Lakma Wijewardana; Thashika Rupasinghe (International Journal of Supply Chain Management, 2013)
This paper aims to evaluate the applicability of lean healthcare concept in to Sri Lankan healthcare supply chains with the intention of achieving process improvement since there is no evidence for lean healthcare, an emerging concept applied in Sri Lankan context. Available literature on lean applied in commercial supply chains, healthcare supply chains and lean applied in healthcare were reviewed and Sri Lankan context is studied mainly through observation and available information. Though it has been proven that lean thinking can be adopted in healthcare it remains a challenge to practically implement with the rigid healthcare structure in Sri Lanka. However the literature review implies that performance excellence can be achieved through lean best practices. Since lean is an emerging concept being applied in healthcare for more than ten years, no effort has made to analyze the applicability in to Sri Lankan context. In addition healthcare supply chain has been defined in different perspectives which cannot be aligned with Sri Lankan scenario.